2013
DOI: 10.1242/jcs.122242
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric immunoglobulin receptor traffics through two distinct apically targeted pathways in primary lacrimal gland acinar cells

Abstract: SummaryThe polymeric immunoglobulin receptor (pIgR) mediates transcytosis of dimeric immunoglobulin A (dIgA) and its release into mucosal secretions. The present study reveals the complexity of the trafficking of pIgR to the apical plasma membrane in epithelial cells with exocrine secretory functions; in rabbit lacrimal gland acinar cells (LGACs), trafficking of pIgR involves both the transcytotic pathway and one arm of the regulated secretory pathway. By specifically tracking pIgR endocytosed from the basolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…The abundant staining of the vesicles in both acinar and ductal cells could indicate that, at these locations, the vesicular trafficking of the melatonin receptor is involved in the transport of the hormone, internalised at the cell base and released from the apex. This phenomenon of transcytosis has been described for both IgA and transferrin in acinar cells (Nashida et al 2009;Xu et al 2013). The transcytosis of melatonin bound to its receptor might parallel the synthesis of melatonin in ductal cells, as reported by Shimozuma et al (2011).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The abundant staining of the vesicles in both acinar and ductal cells could indicate that, at these locations, the vesicular trafficking of the melatonin receptor is involved in the transport of the hormone, internalised at the cell base and released from the apex. This phenomenon of transcytosis has been described for both IgA and transferrin in acinar cells (Nashida et al 2009;Xu et al 2013). The transcytosis of melatonin bound to its receptor might parallel the synthesis of melatonin in ductal cells, as reported by Shimozuma et al (2011).…”
Section: Discussionsupporting
confidence: 54%
“…In addition, in the acinar cells, the vesicles may fuse with the secretory granules to discharge melatonin by the major regulated secretion into the lumen of the glands (Castle & Castle, 1996). The two pathways may co-exist (Xu et al 2013). We assume that, once secreted apically, melatonin is detached from its receptor and becomes a component of the saliva (Kennaway & Voultsios, 1998;Cutando et al 2007), while the receptor is immediately re-absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have identified at least three pathways for apically directed secretion of tear proteins in LGACs: the Rab11a/MyosinVb mediated transcytotic pathway [32] and the Rab3D and/or Rab27b regulated secretory pathways [4042]. Rab3D and Rab27b are predominantly localized to distinct populations of secretory vesicles in the subapical region of LGAC that originate from the trans-Golgi network, although a subpopulation expressing both Rab proteins may exist.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that expression of dominant-negative (DN) myosin-Vb tail directly impairs the movement of transcytotic vesicles and their cargo from Rab11a-enriched apical endosomes to the apical membrane, thus inhibiting transcytosis in LGACs [32]. The Rab11a-enriched apical endosome is well established in the trafficking of another transcytotic cargo receptor, the polymeric immunoglobulin A receptor, responsible for transcytosis of dimeric IgA into tears [42]. In Figure 5, LGACs were transduced with recombinant adenovirus encoding GFP-actin (green) with or without mCherry-myosin Vb tail DN (red), an N-terminal mCherry fluorescent protein fused to a truncated mutant of myosin Vb motor, which associates with vesicle cargo but does not have motor function.…”
Section: Resultsmentioning
confidence: 99%
“…The pIgR which mediate the transepithelial transport of polymeric IgA and secretion of SIgA is expressed by different type of epithelial cells and the resolution of its crystal structure provides new information about multiple conformations used by the secretory component to protect mammals from pathogens (35). The transepithelial trafficking of the pIgR was shown to involve both the transcytotic pathway and one arm of the regulated secretory pathway (36). Factors which participate in the complex regulation of pIgR expression and transcytosis also contribute to optimizing SIgA production and mucosal immunity (37, 38).…”
Section: Iga and Secretory Igamentioning
confidence: 99%